The accidental newlywed game - Burton, Jaci (Burton, Jaci. Boots and bouquets series., 2022)
"Wedding planner Honor Bellini is in Las Vegas for a work conference when she runs into her sister's ex-fiancé, Owen Stone, who's also in town for his craft brewery business. They're both glad to see a familiar face from home...until a night of drinking leads to waking up in bed together--and a marriage certificate from a wedding that neither one of them can recall. Horrified, Owen and Honor agree to an annulment, though after a long drive back to Oklahoma featuring an incendiary kiss, it becomes clear they have red-hot chemistry. But their being together could hurt people they love, so they vow to keep their distance. The problem is, Honor and Owen can't seem to stay apart--or keep their hands off each other. The longer they hold onto this secret, the harder it gets to deny how they really feel--until they both wonder if their accidental marriage has turned into love"--Back cover.